ANALYSIS OF THE SUPPLY OF RED CHILLI (Capsicum Annum. L) IN NORTH SUMATRA PROVINCE - Yayu Juita Agustina Tobing; Lindawati; Salmiah (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
YAYU JUITA AGUSTINA TOBING (207039019) with the thesis title "Analysis of Red Chili (Capsicum Annum. L) Supply in North Sumatra Province". This research was supervised by Dr. Lindawati SP. M.Si as Chair of the supervising Commission and Dr.Ir.Salmiah, MS as member of the supervising commission. Chili in North Sumatra plays a very important role for the government, producers and consumers. Red chilies can help increase regional income in terms of exports and imports. We know that red chilies are able to penetrate the international market both fresh and processed. Availability of planting land, price levels and production costs such as fertilizer prices change every year. This can affect the amount of chili offered in North Sumatra Province. The aim of this research is to determine the influence of independent variables on supply and analyze the short-term and long-term elasticity of red chili supply in North Sumatra Province. The data used in this research is secondary data in the form of a time series starting from 2001 to 2021 (per 6 months). The research method used is distributed lag model analysis. The results of this research are the Prob F-statistic value < significance α = 0.05, namely 0.000011, together with the independent variables in the model, namely the price of red chilies (Pct), the price of red chilies the previous year (Pct-1), area red chili harvest (Lpt), and the price of NPK fertilizer (Hpnt) have a real influence on the dependent variable. significant α = 5%. Based on the probability value, the price of red chilies in the previous year was 0.0408 < α = 0.05 and the area of ​​red chili harvested was 0.0233 < α = 0.05. This shows that the price of red chilies in the previous year and the size of the harvest area have a real influence on the supply of red chilies in North Sumatra Province. Meanwhile, the price of red chilies in year t with a probability of 0.0408 < α = 0.05 and the price of fertilizer in year t with a probability of 0.0633 > α = 0.05 do not have a significant effect because the probability value < α = 0.05. The short term elasticity is 0.051081 < 1, so it is stated as inelastic and the long term elasticity is 0.081358 < 1. In the long term and short term changes in the supply of red chilies in North Sumatra province are smaller than price changes.